2012
DOI: 10.1007/s00253-012-3874-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and characterization of α-amylase inducers in Aspergillus nidulans based on nuclear localization of AmyR

Abstract: AmyR, a fungal transcriptional activator responsible for induction of amylolytic genes in Aspergillus nidulans, localizes to the nucleus in response to the physiological inducer isomaltose. Maltose, kojibiose, and d-glucose were also found to trigger the nuclear localization of GFP-AmyR. Isomaltose- and kojibiose-triggered nuclear localization was not inhibited by the glucosidase inhibitor, castanospermine, while maltose-triggered localization was inhibited. Thus, maltose itself does not appear to be an direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…In A. nidulans, the transglycosylation activity of two α-glucosidases (AgdA and AgdB) with a signal peptide is involved in the conversion from maltose to isomaltose for α-amylase gene induction, although other α-glucosidase(s) with isomaltose-forming activity may exist (Kato et al 2002a, b). The nuclear localization of A. nidulans GFP-AmyR after maltose addition was inhibited by the addition of a α-glucosidase inhibitor, castanospermine (Murakoshi et al 2012). However, in A. oryzae, induction of α-amylase gene expression after maltose addition was not inhibited by the addition of α-glucosidase inhibitors, castanospermine and 1-deoxynojirimycin (data not shown).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…In A. nidulans, the transglycosylation activity of two α-glucosidases (AgdA and AgdB) with a signal peptide is involved in the conversion from maltose to isomaltose for α-amylase gene induction, although other α-glucosidase(s) with isomaltose-forming activity may exist (Kato et al 2002a, b). The nuclear localization of A. nidulans GFP-AmyR after maltose addition was inhibited by the addition of a α-glucosidase inhibitor, castanospermine (Murakoshi et al 2012). However, in A. oryzae, induction of α-amylase gene expression after maltose addition was not inhibited by the addition of α-glucosidase inhibitors, castanospermine and 1-deoxynojirimycin (data not shown).…”
Section: Discussionmentioning
confidence: 44%
“…2c). These results suggested that inducing sugars, such as maltose and glucose, for amylolytic gene expression can trigger the nuclear localization of AmyR in A. oryzae, as observed for AmyR in A. nidulans (Makita et al 2009;Murakoshi et al 2012). On the contrary, GFP fluorescence was observed in the nucleus when the transformant expressing GFP-MalR was cultured in the liquid MM using casamino acids as the carbon source (Fig.…”
Section: Subcellular Localization Of Gfp-amyr and Gfp-malrmentioning
confidence: 74%
See 1 more Smart Citation
“…A direct effect has been reported for xlnR/xyr1 in A. nidulans [162], A. niger [59], T. reesei [106, 155, 163] and T. koningii (208), with ace2 and ace1 in T. reesei [69], and with amyR in A. nidulans [136, 165] and N. crassa [159]. …”
Section: Transcription Factors Directly Involved In Plant Biomass Degmentioning
confidence: 99%
“…CT-rich stretch was shown to be involved in correct initiation of transcription, and a major transcription start point would exist near the CTstretch (Adams andTimberlake, 1990, Punt et al, 1990). Furthermore, five CreA consensus binding sites were present (-548 to -543, -299 to -294, -258 to -253, -207 to -202, and -77 to -72) and one AmyR binding site was present (-101 to -114 (Tani et al, 2001b, Murakoshi et al, 2012. On the other hand, a typical polyadenylation signal, AATAAA, was not found within the 3'-flanking region we determined.…”
Section: Effect Of Disruption Of Asamyr Gene On Amylase Productionmentioning
confidence: 74%